Evolução do uso e ocupação da terra, conflitos de uso e hemerobia na Bacia do Rio São Lourenço no Município de Itaiópolis - SC, no período de 1977/79 a 2011 - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2013)
To meet their needs the man began a steady transformation of the middle giving you other settings according to new interests that arise, which promotes and creates imbalances often conflict situations in land use and occupancy in areas in many cases, they should be protected. Many of these actions taken, especially in watersheds, can generate negative consequences for the whole community, especially when there is lack of planning of land occupation. His aim of this study was to analyze the dynamics of the use and occupation of the land from the use of the concepts of environmental conflict and hemeroby in the basin of the São Lourenço River in the municipality of Itaiópolis - SC, between 1977/79 and 2011. The adoption of this basin is justified by the same form in the area of wealth, fueling the county seat. Regarding the methodological procedures were performed based on bibliographic publications and public institutions and generating maps for the period 1977/79 and 2011. We identified five classes of land use: Urbanized Area, Culture,Forest, Grassland / Rural and Forestry. Classes of Environmental Conflicts adopted were: use area corresponding area overused and underused area. Regarding hemeroby was identified the degree of human interference in the basin, based on the dependence of technological systems from the classes: Ecosystems natural, seminatural Ecosystems, Ecosystem (biotic) anthropogenic 1, Ecosystem (biotic) anthropogenic 2, and Tecno-ecosystems. The results showed that the most significant changes occur in the classes pasture / country, or is semi ecosystems and class culture represented by Ecosystem (biotic) anthropogenic 1, the first of which was the one that lost area (-30.91%) and the second a more expanded (19.96%). The data presented in this analysis reveal that the use and occupation of the land in the basin follow the trend of expansion in the activities related to agribusiness that constitute spatial configuration occurred generally throughout the municipality. The class corresponding usage totaled the largest parcel of land in the basin and the main differences between aptitude and land uses are mainly in areas of permanent preservation.
Keywords: uso da terra; bacia hidrográfica; atividades antrópicas; manancial; land use; watershed; anthropogenic activities; fountainhead; CNPQ::CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA